Research on the matching relationship of municipal solid waste management and alternative fuel in Indonesia's cement industry - Wiharja; Suherman; Syafrudin; Muhammad Abdul Kholiq; Reba Anindyajati Pratama; Muhammad Haqqiyuddin Robbani; Feddy Suryanto (Case Studies in Chemical and Environmental Engineering)
The cement industry in Indonesia, heavily relies on coal, contributing significantly to greenhouse gas (GHG) emissions. Simultaneously, Java Island generates over 23 million tons of municipal solid waste (MSW) annually, with limited utilization for energy recovery. This study evaluates the feasibility of substituting coal with refuse-derived fuel (RDF) from MSW in Java's cement industry, focusing on environmental, economic, and technical aspects. Scenario analyses indicate that substituting 10%, 20%, and 30% of thermal energy with RDF could divert up to 8.7 million tons of MSW from landfills annually, reducing GHG emissions by up to 2.77 million Gg CO₂-eq. These reductions align with Indonesia's environmental policies and global climate commitments under the Paris Agreement. The economic assessment demonstrates the viability of RDF, with potential annual cost savings of up to $421 million. Beyond addressing coal dependency, RDF adoption supports circular economy practices, reduces landfill reliance, and mitigates environmental pollution. However, challenges such as infrastructure gaps and regulatory barriers require attention. This study provides actionable insights to guide policy formulation, foster industry investment, and facilitate the implementation of RDF-based energy solutions. By bridging waste management and sustainable energy practices, the findings contribute to Indonesia's renewable energy goals, emphasizing the practical applications of RDF for a more sustainable future in industrial operations.